Poly Royal 1939 (1939)
[00:00:18] Opening Title [00:00:33] Landscape shots of Cal Poly Campus [00:01:13] "Miss Poly Royal" [00:01:44] Julian A. McPhee [00:02:27] "The Band Plays" [00:02:58] Shot of giant megaphone [00:03:45] "Girls Milk Goats" [00:04:37] "Greased Pigs Chased" [00:05:23] "New "P" Dedicated" [00:05:40] Track meet [00:06:31] Aeronautics" Plane Models [00:06:57] Dairy Judging and exhibit [00:07:44] "Air Conditioning" [00:08:26] "Landscaping" [00:09:27] Agriculture Mechanics [00:10:03] Electrical demonstrations [00:10:48] "Meat Animals" judging [00:15:00] Livestock Judging [00:17:43] "Ladies Drive Nails" [00:18:04] "Climbing Poles" [00:18:36] "Guests Roll Cans" [00:19:32] Poly Royal Barbecue [00:21:00] Rodeo [00:22:16] End footage